2007
DOI: 10.2320/matertrans.maw200702
|View full text |Cite
|
Sign up to set email alerts
|

Substance Flow Analysis of Indium for Flat Panel Displays in Japan

Abstract: Substance flow analysis (SFA) of indium has been conducted in this study. The purpose of this study is to identify the relevant issues for the development of an efficient indium recycling system by performing SFA of indium supplied for indium-tin oxide (ITO) processing as transparent electrodes, which accounts for 86.9% of the total indium demand. In this study, as part of the development of substance and material flow data, (1) data on the flow of indium was collected and reviewed, (2) the amount of dissipate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…4) Consequently, it is not possible to directly estimate the indium contained in final products from the annual demand for indium for ITO. Therefore, in this work, the amount of indium in final products was estimated using a bottom-up approach.…”
Section: Estimation Of the Amount Of Indium In Finalmentioning
confidence: 99%
See 1 more Smart Citation
“…4) Consequently, it is not possible to directly estimate the indium contained in final products from the annual demand for indium for ITO. Therefore, in this work, the amount of indium in final products was estimated using a bottom-up approach.…”
Section: Estimation Of the Amount Of Indium In Finalmentioning
confidence: 99%
“…Nakajima et al focused on the manufacturing processes for flat panel displays to investigate the flow of indium in 2004. 4) However, this study covered the flow of indium in Japan in one year only and did not consider the flow after the final products had been manufactured. Endo et al projected the depletion of indium based on the results of indium flow in mining and smelting and the potential demand for LCD products.…”
Section: Introductionmentioning
confidence: 99%
“…1417) In 2007, Nakajima 15) successfully analysed indium flow for flat panel display in Japan. They showed that around 220 t-In out of 470 t-In used in the production of transparent electrodes is dissipated or potentially dissipated.…”
Section: Introductionmentioning
confidence: 99%
“…During the last year, 2014, SFAs for other precious metals such as palladium and silver were also reported. 15,16) As Taiwan is one of the top countries in the world that has high demand for indium, it is very interesting to understand the domestic flow of this substance. In this study, we employed SFA to assess indium flow in Taiwan in different stages including import, export, manufacturing, usage, recycling, and disposal, for the year 2011.…”
Section: Introductionmentioning
confidence: 99%
“…9) In Japan, the authors have developed the MFA/SFA methods based on the waste inputoutput (WIO) 10,11) table, and they have collected and assessed data on the material/substance flow. [12][13][14] This study focuses on manganese (Mn), which is one of the seven rare metals stockpiled by the National Stockpile Program; the data on Mn flow is collected and assessed. Figure 1 shows the demand for Mn in Japan in 2004.…”
Section: Introductionmentioning
confidence: 99%